Developing an Assessment Checklist - Maistro, Maria (Improving University Science Teaching and Learning, 2023)
The goal of this project was to prepare an assessment checklist for the Information Retrieval (IR) course at the department of Computer Science in the academic year 2019/2020. This project was motivated by some observations regarding the previous edition of the IR course: in the 2018/2019 edition there was a clear mismatch between students and teachers expectations regarding the assignment. The students were struggling in understanding how to structure and write a good quality assignment. Furthermore, even if the students were instructed with guidelines on how to give feedback, they were struggling also in providing useful feedback to their peers. With the proposed assessment checklist, we aimed at guiding and helping students in structuring their assignment and peer reviews. This paper is organised as follows: Section 1 describes the course during which the project was carried out; Section 2 presents the project goals and motivations; Section 3 carefully describes how the project was conducted; Section 4 reports some analysis about the project results; and Section 5 presents conclusions and future challenges.